2006
DOI: 10.3748/wjg.v12.i23.3751
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine does not prevent post-endoscopic retrograde cholangiopancreatography hyperamylasemia and acute pancreatitis

Abstract: N-acetylcysteine fails to demonstrate any significant preventive effect on post-ERCP pancreatitis, as well as on serum and urine amylase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…N-acetylcysteine a free radical scavenger inhibits capillary endothelial injury mediated by oxygen-derived free radicals. Two recent studies from Poland and Greece concluded that N-acetylcysteine failed to demonstrate any significant preventive effect on PEP, nor asymptomatic serum or urine amylase elevations [113,114] . An inhibitor of the platelet activating factor diminished experimental acute pancreatitis.…”
Section: Category 3: Markers Of Systemic Inflammationmentioning
confidence: 99%
“…N-acetylcysteine a free radical scavenger inhibits capillary endothelial injury mediated by oxygen-derived free radicals. Two recent studies from Poland and Greece concluded that N-acetylcysteine failed to demonstrate any significant preventive effect on PEP, nor asymptomatic serum or urine amylase elevations [113,114] . An inhibitor of the platelet activating factor diminished experimental acute pancreatitis.…”
Section: Category 3: Markers Of Systemic Inflammationmentioning
confidence: 99%
“…Amongst the 22 papers, 19 (86%) scored 3 and only three studies [17,25,31] scored 2 or lower according to the Jadad score. Table 1 presents controlled clinical trials of antioxidants in patients with AP or CP.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the rate of PEP was not significantly reduced. In addition, urine amylase activity, total bilirubin, alanine, aspartate aminotransferases and white blood cells showed no change [31] . In the other double-blind, placebo-controlled trial (n = 256), patients received intravenous NAC at a loading dose of 70 mg/kg 2 h before and 35 mg/kg at 4-h intervals for a total of 24 h after the procedure.…”
Section: Antioxidants In Pepmentioning
confidence: 91%
See 1 more Smart Citation
“…N-acetyl cysteine is a free radical cleaner stimulating glutathione synthesis. It was used as IV before and after ERCP in two randomized controlled trials and was not found superior to placebo in the prevention of PEP and hyperamylasemia (125,126).…”
Section: Drugs Reducing Inflammationmentioning
confidence: 99%